2002
DOI: 10.1007/bf03177322
|View full text |Cite
|
Sign up to set email alerts
|

Parent participation in children’ school readiness: The effects of parental self-efficacy, cultural diversity and teacher strategies

Abstract: Many early intervention programs have been shaped by the notion that children's development should be studied in the contexts offamily and community. Reciprocal parent-child interaction is a key feature ofchild development in those contexts. Parent involvement, parental self efficacy and parenting style are factors that influence parent-child interactions and contribute to early development, the transition to school, andfuture child outcomes. This study examined parent factors and teacher strategies to foster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 48 publications
0
48
0
4
Order By: Relevance
“…A parent with a high level of self-efficacy has a high level of self-confidence in their ability to act as a parent, is willing to invest in this task, is inclined to believe that they have the ability to positively affect the development and behavior of his child, and to meet the child's needs in both an efficient and correct manner (Jones & Prinz, 2005;Pelletier& Brent, 2002). Parental self-efficacy has been found to be associated with positive parenting strategies (Giallo, Kienhuis, Treyvaud & Matthews, 2008).…”
Section: Maternal Self-efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…A parent with a high level of self-efficacy has a high level of self-confidence in their ability to act as a parent, is willing to invest in this task, is inclined to believe that they have the ability to positively affect the development and behavior of his child, and to meet the child's needs in both an efficient and correct manner (Jones & Prinz, 2005;Pelletier& Brent, 2002). Parental self-efficacy has been found to be associated with positive parenting strategies (Giallo, Kienhuis, Treyvaud & Matthews, 2008).…”
Section: Maternal Self-efficacymentioning
confidence: 99%
“…Mothers who view themselves as having high levels of selfefficacy are more likely to demonstrate a warm and responsive style of parenting combined with strict discipline and control over the child's behavior. Parental efficacy has been linked to child adjustment in various areas (Jones &Prinz, 2005) including academic achievement (Pelletier & Brent, 2002). With regard to behavior, it has been found that children of parents with high parental efficacy tend to report fewer behavioral problems than children of parents with low parental efficacy (Bogenschneider, Small & Tsay, 1997).…”
Section: Maternal Self-efficacymentioning
confidence: 99%
“…Yet the pendulum swings, and in June 2014 the Chief Inspector of schools in England stated that parents who did not read to their children should be fined. Whilst over the years, the home has played a part in supporting the development of children's reading (Auerbach, 1989;Baghban, 1984;Hannon, 1995;Taylor and Dorsey-Gaines, 1988;Neumann andRoskos, 1997, Petellier andBrent 2002), in the main it has been mothers who have been the main supporters of their children's home reading activity (Mace, 1998). Hartas (2011) identified that literacy development in young children at age five is more directly related to the mother's level of education than it is to family income, also a finding of a study by Nutbrown et al, (2005) which also identified considerable involvement of fathers in their young children's literacy at home (Morgan et al, 2009) The literature on home reading in the UK following World War Two is sparse, yet something of the 'therapeutic' potential of books was seen to be important (Moore, 1943).…”
Section: How Has Reading Been Part Of Family Life In the Uk Throughoumentioning
confidence: 99%
“…Children can even teach their parents some of the important questions that have been "hidden by the answers" (in the James Baldwin sense). Parental participation is an important element of excellence in education [11]. Building on concepts like Web-based Inquiry Science Environment [12], computing in an existential education environment can be collaborative.…”
Section: Universal Access Personal Customization and Diy As A Form mentioning
confidence: 99%